PKM PELATIHAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA DAN PEMASARAN ONLINE KELOMPOK USAHA PENGRAJIN TENUN DI BALI - I Gusti Ayu Ratih Permata Dewi; Putu Yudha Asteria Putri; Putu Gede Wahyu Satya Nugraha (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The Ngaben ceremony is a cremation tradition in Balinese culture, Indonesia. The weaving used in this ceremony has special meaning and symbolism. The selection of weaving for the Ngaben ceremony is generally adjusted to local beliefs and traditions. Several types of weaving that are generally used in the Ngaben ceremony involve certain colors and motifs that have deep meaning. From the raw material, yarn will become woven fabric. Weaving craftsmen in Kumbasari Market, Denpasar City, Bali can produce various kinds of woven fabrics for the Ngaben ceremony. The community service program is carried out in the trading and production business of weaving crafts